Electropolymerization of Thiophene in a Bis(fluorosulfonyl)amide Based Phosphonium Ionic Liquid. (10th January 2017) - Nishihata, Keiichi; Tsunashima, Katsuhiko; Ono, Yasushi; Matsumiya, Masahiko
Abstract : The electropolymerization of thiophene in room-temperature ionic liquids based quaternary phosphonium cations together a bis(fluorosulfonyl)amide anion and the characterizations of the obtained polythiophene films are presented in this report. A bis(fluorosulfonyl)amide anion based phosphonium ionic liquid gave relatively large voltammetric response for the electropolymerization of thiophene. The polythiophene ﬁlm thus obtained also showed relatively high CV cycling property and smooth surface.